A 900 m‐deep borehole from Boiano intermontane basin (southern Apennines, Italy): Age constraints and palaeoenvironmental features of the Quaternary infilling. (23rd November 2020) - Amato, Vincenzo; Aucelli, Pietro P. C.; Cesarano, Massimo; Rosskopf, Carmen M.; Cifelli, Francesca; Mattei, Massimo
Abstract : The Boiano Basin is one of the largest Quaternary intermontane basins of the central‐southern Apennines within one of the most tectonically active areas of the Mediterranean region. In order to reconstruct its entire Quaternary stratigraphic, tectonic, and palaeoenvironment evolution, lithofacies and palaeomagnetic analyses have been performed on a 900 m‐deep borehole (CP1) drilled in the southwestern sector of the basin. The Quaternary succession consists of an alternating of alluvial fan and fluvial–marshy deposits for a total thickness of 240 m, unconformably laying on Lower Miocene deposits of the Sannio Unit, thrusted on upper Miocene deposits of the Molise Flysch. In addition, the stratigraphic study and facies distribution of 29 intermediate and shallow wells drilled in the basin, allowing us to define the thickness and lithofacies variations of the Quaternary sedimentary units inside the entire Boiano Basin in the sector of Campochiaro alluvial fan. Our results demonstrate that the Boiano Basin infilling started during the late Early Pleistocene (c. 1.1 Ma) and developed with variation in lithofacies distribution and thickness. The first depositional unit (Early Pleistocene–early Middle Pleistocene in age) was palustrine and fluvial–marshy, the second (Middle Pleistocene in age) was characterized by the occurrence of the first cycle of alluvial fan deposition, the third (late Middle Pleistocene in age) was newly palustrine and fluvial marshy and, finally, the fourth recorded two cycles of alluvial fan deposition (late Middle Pleistocene and Late Pleistocene in age, respectively), interspersed by short periods of palustrinity, tephra layers deposition, and palaeosols development. The study allows the hypothesizing that the Quaternary infilling was accommodated within a graben (or semigraben) structure, affected mainly by extensional fault systems localized in the inner part of the basin and secondly by fault systems bounding the basin. Abstract : Facies analyses and chrono‐stratigraphy of deep and shallow boreholes and outcroppings of the intermontane basins are the key to understand their palaeoenvironmental and tectonic Quaternary evolution. Geological cross‐sections throw boreholes allow detecting buried faults, mainly located in the inner part of the basin, leached to the Northern Matese System Faults, one of the most seismogenic structures of the Southern Apennine.